Design and Implementation of the Network-based Computer Antivirus Applications - Erniza; Darma Setiawan Putra; Agustinus Suwodjo; Muhammad Abrar (Mulia International Journal in Science and Technical, 2018)
The current era of globalization of security needs to be considered because danger can come from anywhere. Likewise, with a computer system, a computer also needs protection, because a lot of data is stored in it, and the information is essential data. Computers and mobile phones are currently widely used by everyone, where a lot of info is stored therein and connected to the internet. Today's internet network has become an essential requirement because all services are on the internet. With the development of internet technology, the data is more easily accessed and also increasingly vulnerable because if it is not protected it will enter various viruses that can cause data to be lost or damaged. This era is an era where viruses have developed rapidly, not just from academic research but have become a common problem for computer users in the world. This loss effect is increasingly becoming with the widespread use of the internet as a global communication channel between computer users around the world, based on CSI / FB survey results. With the development of the virus, the antivirus is needed by technology users. An antivirus is a form of security efforts from unwanted virus attacks. Through the development of internet-based antivirus, the user can easily find out the behavior of the virus and can immediately prevent it, so that the data is saved.